Remote Work Has to Be Engaging: Why Compensation and Career Development Alone Are Not Enough to Drive Performance - Heni Kesumayani; Rita Rita (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Remote work has expanded rapidly in Indonesia and created new challenges for sustaining employee performance in digitally mediated work settings. This study examines the role of employee engagement in mediating the effects of compensation and career development on the performance of remote workers. A quantitative approach was employed using survey data from 200 Indonesian remote workers, and the relationships among variables were analyzed through Partial Least Squares Structural Equation Modeling. The results show that compensation and career development both have significant positive effects on employee engagement, while employee engagement has a strong positive effect on employee performance. The direct effect of compensation on performance is not significant, indicating that its influence operates mainly through engagement. In contrast, career development affects performance both directly and indirectly through engagement. These findings indicate that employee engagement is a key mechanism linking organizational support to remote employee performance. The study implies that organizations should not rely solely on financial rewards, but also provide clear career pathways, continuous learning opportunities, regular feedback, and meaningful recognition to strengthen engagement and improve performance in remote work environments.